Comparison of cardiovascular outcomes of moderate to severely calcific de novo coronary lesion preparation for stent implantation using rotational atherectomy in conjunction with cutting balloon versu. (14th October 2021) - Gedela, M G; Giustino, G G; Kyaw, H K; Johal, G J; Hooda, A H; Sartori, S S; Qiu, H Q; Mehran, R M; Kini, A K; Sharma, S S
Abstract: Background: Previous studies showed the combined rotational atherectomy (RA) and cutting balloon angioplasty (CBA) strategy was associated with favourable cardiovascular outcomes compared to RA and plain balloon angioplasty (PBA) for adequate lesion preparation before stent implantation in moderate to severely calcified coronary lesions. However, these studies were limited by small sample size. Purpose: To assess clinical outcomes in a large group of patients with moderate to severely calcified de novo severe coronary artery stenoses using RA followed by CBA (RA+CBA) compared to RA followed by PBA (RA+PBA) before 2.5–3.5 mm diameter stent implantation. Methods: We conducted a retrospective analysis of 1852 patients with moderate to severely calcified de novo severe coronary artery stenosis who underwent RA+CBA (n=372) or RA+PBA (n=1480) before 2.5–3.5 mm stent implantation. Death, myocardial infarction (MI), target vessel revascularization (TVR), stent thrombosis (ST), and major adverse cardiovascular events (MACE) were calculated at 1-year. Standard multivariable covariate adjusted hazard ratios (HR) were performed. Results: At 1-year follow-up, the unadjusted MACE [HR: 1.58 (1.14–2.21); p=0.007] was significant in RA+CBA group compared to RA+PBA group, even after adjusted for multiple variables [HR: 1.61 (1.11–2.35); p=0.013] (Figure 1A). This was mainly driven by TVR [Unadjusted HR: 1.76 (1.16–2.68); p=0.008 and adjusted HR: 1.64 (1.01–2.67); p=0.045] (Figure 1B). However, other adjusted outcomes including death [HR: 1.25 (0.63–2.50); p=0.521], MI [HR: 1.71 (0.77–3.77); p=0.188], and ST [HR: 2.11 (0.64–6.95); p=0.221] were not significant between both groups. There was no significant difference in complications including coronary artery dissection, side branch closure, coronary perforation, slow flow/no flow, abrupt vessel closure, post procedure MI, blood transfusion or bleeding in between the two groups. Conclusion: In moderate to severely calcific de novo severe coronary artery stenosis lesion preparation before 2.5–3.5 mm stent implantation, RA+CBA strategy is associated with a higher risk of major adverse cardiovascular events compared to RA+PBA strategy at 1-year follow-up. FUNDunding Acknowledgement: Type of funding sources: None.